Targeting hygiene a practical guide to hygiene and safety for food handlers (CERT, 1988)
The book can help business managers to set and maintain hygiene and safety standards which will ensure customer confidence and wellbeing at all time. Its easy-to-follow instructions, illustrations and case studies make it ideal for training staff and students.